PENGARUH MODEL COOPERATIVE LEARNING TIPE JIGSAW TERHADAP KEMAMPUAN PASSING ATAS BOLA VOLY - Yulianto Yulianto; Victor G Simanjuntak; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe purpose of this study was to determine the contribution of Jigsaw cooperative learning ability to volleyball pairs in students at SMPN 6 Pontianak. The method used in this study was an experiment involving two independent variables of exercise variation and bound variation, namely passing on volleyball. The population of the students of SMP Negeri 6 Pontianak, as many as 30 students, took the sample using the cooperative learning method of jigsaw type, the study took all of the population, with a total sample of 30 students. This research technique uses tests and measurements, namely tests with a lattice measurement measurement instrument over the volleyball. Data analysis using t-test formula. The results of this study were 12,539> t table (1,699), so that the alternative hypothesis (Ha) was accepted and the value hypothesis (Ho) was rejected. This means that there is an influence of the Jigsaw Cooperative Learning Model there is the result of passing a volleyball on the students of SMP Negeri 6 Pontianak.Keywords: Cooperative Learning Model, Passing Over, Volleyball